2001
DOI: 10.1046/j.1439-0272.2001.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of microsurgical subinguinal varicocelectomy in infertile men

Abstract: The present study assesses the clinical outcome of microsurgical subinguinal varicocelectomy in infertile men, especially with regard to sperm count, motility and fertility. Between June 1990 and October 1998, 272 patients had subinguinal microsurgical varicocelectomy operations for clinical varicoceles, and their long-term results were assessed. In nearly all the patients there was a significant improvement in sperm count and sperm motility after 3 and 6 months. Very few complications arose from this procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 16 publications
6
18
1
4
Order By: Relevance
“…To compare spontaneous pregnancy rates among the techniques used for varicocele repair, the approaches in this review included retroperitoneal high ligation (Palomo technique) with 10 studies (Cockett et al, 1984; Baker et al, 1985; Menchini‐Fabris et al, 1985; Rageth et al, 1992; Hirokawa et al, 1993; Nieschlag et al, 1993; Madgar et al, 1995; Shlansky‐Goldberg et al, 1997; Çayan et al, 2000; Watanabe et al, 2005), microsurgical subinguinal or inguinal technique with 12 studies (subinguinal, 7; inguinal, 5; 1 study to compare both approaches; Goldstein et al, 1992; Ito et al, 1993; Marmar and Kim, 1994; Çayan et al, 2000, 2002; Jungwirth et al, 2001; Kamal et al, 2001; Perimenis et al, 2001; Kumar and Gupta, 2003; Orhan et al, 2005; Watanabe et al, 2005), laparoscopic varicocelectomy with 5 studies (Mehan et al, 1992; Jarow et al, 1993; Enquist et al, 1994; Milad et al, 1996; Watanabe et al, 2005), radiologic embolization with 6 studies (Vermeulen et al, 1986; Yavetz et al, 1992; Nieschlag et al, 1993; Ferguson et al, 1995; Shlansky‐Goldberg et al, 1997; Nabi et al, 2004), and macroscopic inguinal (Ivanissevich) with 3 studies (Newton et al, 1980; Marks et al, 1986; Yavetz et al, 1992). To compare postoperative recurrence and hydrocele formation rates among the techniques used for varicocele repair, the analysis included retroperitoneal high ligation with 4 studies (Yavetz et al, 1992; Çayan et al, 2000; Ghanem et al, 2004; Watanabe et al, 2005), microsurgical technique with 10 studies (subinguinal, 6; inguinal, 4; 1 study to compare both approaches; Goldstein et al, 1992; Ito et al, 1993; Marmar and Kim, 1994; Çayan et al, 2000; Jungwirth et al, 2001; Kamal et al, 2001; Ghanem et al, 2004; Orhan et al, 2005; Watanabe et al, 2005), laparoscopic varicocelectomy with 5 studies (Mehan et al, 1992; Jarow et al, 1993; Enquist et al, 1994; Milad et al, 1996; Watanabe et al, 2005), radiologic embolization with 3 studies (Yavetz et al, 1992; Nabi et al, 2004; Tanahatoe et al, 2004), and macroscopic ...…”
Section: Methodsmentioning
confidence: 99%
“…To compare spontaneous pregnancy rates among the techniques used for varicocele repair, the approaches in this review included retroperitoneal high ligation (Palomo technique) with 10 studies (Cockett et al, 1984; Baker et al, 1985; Menchini‐Fabris et al, 1985; Rageth et al, 1992; Hirokawa et al, 1993; Nieschlag et al, 1993; Madgar et al, 1995; Shlansky‐Goldberg et al, 1997; Çayan et al, 2000; Watanabe et al, 2005), microsurgical subinguinal or inguinal technique with 12 studies (subinguinal, 7; inguinal, 5; 1 study to compare both approaches; Goldstein et al, 1992; Ito et al, 1993; Marmar and Kim, 1994; Çayan et al, 2000, 2002; Jungwirth et al, 2001; Kamal et al, 2001; Perimenis et al, 2001; Kumar and Gupta, 2003; Orhan et al, 2005; Watanabe et al, 2005), laparoscopic varicocelectomy with 5 studies (Mehan et al, 1992; Jarow et al, 1993; Enquist et al, 1994; Milad et al, 1996; Watanabe et al, 2005), radiologic embolization with 6 studies (Vermeulen et al, 1986; Yavetz et al, 1992; Nieschlag et al, 1993; Ferguson et al, 1995; Shlansky‐Goldberg et al, 1997; Nabi et al, 2004), and macroscopic inguinal (Ivanissevich) with 3 studies (Newton et al, 1980; Marks et al, 1986; Yavetz et al, 1992). To compare postoperative recurrence and hydrocele formation rates among the techniques used for varicocele repair, the analysis included retroperitoneal high ligation with 4 studies (Yavetz et al, 1992; Çayan et al, 2000; Ghanem et al, 2004; Watanabe et al, 2005), microsurgical technique with 10 studies (subinguinal, 6; inguinal, 4; 1 study to compare both approaches; Goldstein et al, 1992; Ito et al, 1993; Marmar and Kim, 1994; Çayan et al, 2000; Jungwirth et al, 2001; Kamal et al, 2001; Ghanem et al, 2004; Orhan et al, 2005; Watanabe et al, 2005), laparoscopic varicocelectomy with 5 studies (Mehan et al, 1992; Jarow et al, 1993; Enquist et al, 1994; Milad et al, 1996; Watanabe et al, 2005), radiologic embolization with 3 studies (Yavetz et al, 1992; Nabi et al, 2004; Tanahatoe et al, 2004), and macroscopic ...…”
Section: Methodsmentioning
confidence: 99%
“…One patient with maturation arrest established pregnancy. Jungwirth et al (19) assessed the long-term results in 272 patients who had undergone subinguinal microsurgical varicocelectomy operations for clinical varicoceles. In nearly all the patients, there was a significant improvement in sperm count and sperm motility after 3 and 6 months.…”
mentioning
confidence: 99%
“…[16][17][18] Kattan et al 19 reported that the proportion of cases in which preservation of the artery was possible after conventional laparoscopic varicocele ligation was 55%. Although we had tried to preserve the testicular artery and lymphatics in all cases, the testicular artery was spared in just five (26.3%) patients who underwent LESS.…”
Section: Discussionmentioning
confidence: 99%